2000
DOI: 10.1136/ard.59.12.954
|View full text |Cite
|
Sign up to set email alerts
|

No increased mortality in patients with rheumatoid arthritis: up to 10 years of follow up from disease onset

Abstract: Objective-To investigate mortality, functional capacity, and prognostic factors for mortality in an inception cohort of patients with recently diagnosed RA followed up for up to 10 years. Methods-The observed mortality of this inception cohort with recently diagnosed RA, was analysed in relation to the expected mortality, calculated with the aid of life tables of the general population of the Netherlands (matched for age and sex). Functional capacity was measured by the Health Assessment Questionnaire. Prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
2
10

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 24 publications
5
60
2
10
Order By: Relevance
“…Also, the observed mortality rate was equal to that in the general population. This finding is consistent with those of some previous studies (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…Also, the observed mortality rate was equal to that in the general population. This finding is consistent with those of some previous studies (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…While IA patients are treated with disease modifying anti-rheumatic drugs (DMARDs) and biologic agents that reduce disease activity, multiple studies have demonstrated increased cardiovascular (CV) risk despite conventional anti-rheumatic therapy [4][5][6][7]. Several studies of rheumatoid arthritis (RA) patients with disease durations of less than 5 years demonstrated an increased CV risk, suggesting this excess risk is an early feature of RA [4,[8][9][10][11]. The risk appears to accumulate over time and persists after adjustment for other cardiovascular risk factors (relative risk of MI is greater than three after 10 years of having the disease) [6,12] suggesting that RA independently doubles the hazard for myocardial infarction and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…Three further RA risk loci have been identified recently, including the STAT4 gene [7][8][9], loci in the 6q23 [10][11] and TRAF1/C5 [12][13]. As RA is a major cause of disability and is even correlated with increased mortality in severe cases [14]. Identification of genetic risk factors of RA may help to understand basic mechanisms of autoimmunity and may be helpful in the development of targeted diagnostics and therapeutics.…”
Section: Introductionmentioning
confidence: 99%